2016
DOI: 10.1149/2.0061612jes
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Citric Acid in Perfecting Platinum Monolayer on Palladium Nanoparticles during the Surface Limited Redox Replacement Reaction

Abstract: Cu-mediated-Pt-displacement method that involves the displacement of an underpotentially deposited (UPD) Cu monolayer by Pt has been extensively studied to prepare core-shell catalysts. It has been found that Pt clusters instead of a uniform Pt monolayer were formed in the gram batch synthesis. With a suitable surfactant, such as citric acid, the Pt shell could be much more uniform. In this study, the role of citric acid in controlling the Cu-Pt displacement reaction kinetics was studied by electrochemical tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…In terms of shell thickness, a monolayer is in theory ideal and has been elaborately achieved through the use of different methods including the UPD, the ALD and the sputtering deposition, exhibiting better catalytic activities for ORRs than pure Pt due to strain and ligand effects [45,59,65,66,299,301,304,334]. However, experimental results have indicated that optimum Pt thicknesses involve 2~3 atomic layers, rather than the monolayer for catalytic performances [297,299,409,410]. For example, a Pd@Pt catalyst with a two atomic layer shell was found to exhibit a higher mass activity normalized by the mass of Pt and Pt-group metals (MA P , MA PGM ) and a higher specific activity (SA) than catalysts with a monolayer shell [297,409].…”
Section: Pd As Corementioning
confidence: 99%
“…In terms of shell thickness, a monolayer is in theory ideal and has been elaborately achieved through the use of different methods including the UPD, the ALD and the sputtering deposition, exhibiting better catalytic activities for ORRs than pure Pt due to strain and ligand effects [45,59,65,66,299,301,304,334]. However, experimental results have indicated that optimum Pt thicknesses involve 2~3 atomic layers, rather than the monolayer for catalytic performances [297,299,409,410]. For example, a Pd@Pt catalyst with a two atomic layer shell was found to exhibit a higher mass activity normalized by the mass of Pt and Pt-group metals (MA P , MA PGM ) and a higher specific activity (SA) than catalysts with a monolayer shell [297,409].…”
Section: Pd As Corementioning
confidence: 99%
“…Most of their work focused on the use of these catalysts as efficient oxygen reduction cathodes, although they also studied them as alcohol and CO anodes as well. They were the first to scale up this preparation route to practical carbon-supported catalysts [90], soon followed by other work [53,98,99]. On the other hand, Sotiropoulos and co-workers continued the partial galvanic replacement of metal poly-layers (Cu, Pb, Fe, Co, Ni) by more noble metals (mainly Pt, Au, Ru, Ir) and used the resulting electrodes in a number of fuel cell and electrolysis relevant reactions (oxygen reduction, methanol oxidation, borohydride oxidation, hydrogen and oxygen evolution) [67,68,[100][101][102][103][104][105][106][107][108][109][110][111][112][113].…”
Section: Nanoparticle and Catalytic Layer Applicationsmentioning
confidence: 99%
“…The role of citric acid in controlling the uniformity of Pt monolayers on Pd was studied by electrochemical techniques and theoretical approaches 53 . It was found that citric acid strongly adsorbed on Pd, Pt, Cu@Pd (Cu UPD layer) and Pd@Pt surfaces, especially in the double layer region in acid solutions.…”
Section: Gram Batch Synthesismentioning
confidence: 99%
“…The durability of core-shell electrocatalysts were evaluated on RDE using a square-wave signal between 0.65 and 1.00 V for 5 s at each potential. After 10000 cycles, the Pt mass activity of Pd@Pt/C dropped by 16% 53 . This result suggested that Pd@Pt/C was even more stable than Pt/C, which degraded 42% under the same testing condition.…”
Section: Gram Batch Synthesismentioning
confidence: 99%